Resilience Training for Burnout Reduction Among Emergency Department Health Workers: A Systematic Review - Fathiariani, Liza; Bella, Natha; Amirza, Nura Shara; Radhiah, Radhiah (Asian Journal of Public Health and Nursing, 2025)
Background: Emergency department (ED) healthcare workers are at elevated risk of burnout due to high workloads, time pressure, and repeated exposure to trauma. Resilience training has emerged as a promising intervention, yet its specific effectiveness in ED settings has not been comprehensively reviewed. Methods: This systematic review evaluated 20 studies (from an initial pool of 1,120 articles) that met predefined inclusion criteria, encompassing randomized controlled trials, quasi-experimental studies, cohort designs, and qualitative research. Literature searches were conducted across PubMed, ScienceDirect, and Google Scholar for studies published between 2014 and 2024. Data were extracted on intervention type, duration, burnout assessment tools (e.g., MBI, CBI), and psychological outcomes. Results: Resilience training—particularly mindfulness-based interventions and cognitive-behavioral techniques—was associated with a 25–30% reduction in burnout scores, especially in the emotional exhaustion domain. Participants also reported improvements in coping strategies and psychological well-being. However, heterogeneity in intervention formats (ranging from 4 to 12 weeks) and outcome measures limited direct comparisons across studies. Conclusions: Resilience training appears to be an effective strategy for mitigating burnout among ED healthcare workers. To enhance its impact, future research should prioritize the development of standardized protocols, integration into hospital policies, and assessment of long-term outcomes. Digital formats, such as app-based or microlearning modules, also warrant further investigation for broader accessibility and scalability.